Describing the values of Filipino adolescents: a comparison with pan-cultural norms. (1st September 2014) - Bernardo, Allan B. I.; Clemente, Jose Antonio R.; Liem, Gregory Arief D.
Abstract : An etic approach was used to describe the values of Filipino adolescents and to show how pan-cultural comparisons using a values survey can complement emic approaches to studying values. Participants were 752 adolescents who answered the Portrait Values Questionnaire (PVQ). The results indicate that PVQ has structural validity and adequate internal consistency. Ranks of the value types were compared with pan-cultural student norms; the results indicate that (a) Filipino adolescents' value type hierarchies are substantially similar (same top, same middle, same bottom ranked values), and (b) Filipino adolescents gave higher rankings for hedonism and stimulation and lower ranking for achievement.